1995
DOI: 10.1051/apido:19950306
|View full text |Cite
|
Sign up to set email alerts
|

Social parasitism in bumble bees (Hymenoptera, Apidae): observations of Psithyrus sylvestris in Bombus pratorum nests

Abstract: Summary — Females of Psithyrus sylvestris (Lep) were introduced into free foraging colonies of their host Bombus pratorum (L) and interactions of hosts and parasites during the introduction period, and their behaviour during colony development were studied. The reactions of the host bees to the introduction of social parasites in 3 observed colonies ranged from aggressive to non-aggressive behaviour. Psithyrus females cohabited with host bees for several weeks following their introduction. They did not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 2 publications
0
15
0
4
Order By: Relevance
“…Avoidance was also used by B. sylvestris females during their initial introduction into the B. terrestris nest, although they responded more aggressively to attacks by these workers. Küpper and Schwammberger (1995) also found that B. sylvestris inquilines invaded nests of B. pratorum without aggression. The B. sylvestris female appeared to change her strategy when introduced into the B. terrestris colony.…”
Section: Strategies Used By the Inquiline B Sylvestrismentioning
confidence: 83%
See 2 more Smart Citations
“…Avoidance was also used by B. sylvestris females during their initial introduction into the B. terrestris nest, although they responded more aggressively to attacks by these workers. Küpper and Schwammberger (1995) also found that B. sylvestris inquilines invaded nests of B. pratorum without aggression. The B. sylvestris female appeared to change her strategy when introduced into the B. terrestris colony.…”
Section: Strategies Used By the Inquiline B Sylvestrismentioning
confidence: 83%
“…However a more complete mimetism may only be possible when these inquilines nest with their natural host, B. pratorum. In this situation, B. sylvestris engaged in "head-rubbing", which consisted in moving close to a host bumblebee of B. pratorum and gently rubbing against her head or thorax (Küpper and Schwammberger, 1995). According to the authors, pheromonal communication for the establishing of dominance may be involved.…”
Section: Strategies Used By the Inquiline B Sylvestrismentioning
confidence: 99%
See 1 more Smart Citation
“…(Ps.) campestris) are nonaggressive (Hoffer 1888;Sladen 1912;Fisher 1988), whereas aggressive and non-aggressive interactions have been observed against cuckoos that produce dodecyl acetate (Sladen 1912;Van Honk et al 1981;Küpper and Schwammberger 1995). Similar compounds (e.g., decylacetate and decyl butyrate) also are found in the enlarged Dufour's glands of slave-making Formica and Polyergus ants, where they act as repellents during raids (Regnier and Wilson 1971;Graham et al 1979;D'Ettorre et al 2000;Tsuneoka and Akino 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Colonies of the bumble bee Bombus terrestris, for example, are often parasitized by the cuckoo bumble bee Bombus (Psithyrus) vestalis, which kills the host colony's queen. The B. terrestris workers then rear both the B. vestalis progeny and those of their lost mother (Kupper andSchwammberger, 1995, Erler andLattorff, 2010). Ants are also common victims of social parasitism; inquiline ants live in the nests of other species where the host workers rear the inquiline's progeny as well as their own (reviewed in Buschinger, 2009).…”
Section: Introductionmentioning
confidence: 99%